THE IMPLEMENTATION OF TECHNOLOGY BASED INFORMATION SYSTEMS IN ISLAMIC BANKING TO IMPROVE CUSTOMER SERVICES - Aswadi Lubis; Muhammad Isa; M. Fauzan (RADJA PUBLIKA, 2025)
The implementation of technology-based information systems in Islamic banking is a crucial step in improving the quality of customer service. By leveraging the rapid development of information technology, Islamic banks can improve operational efficiency, accelerate transaction processes, and facilitate customer access to services. An integrated information system enables banks to provide faster, more accurate, and more transparent services, in accordance with Sharia principles that prioritize fairness and openness. Furthermore, technology also plays a role in supporting innovation in a wider variety of Islamic banking products, such as digital banking services and technology-based financing products, which provide ease and convenience for customers in conducting transactions. The application of this technology is expected to increase customer satisfaction, strengthen the competitiveness of Islamic banking, and expand the reach of services both nationally and internationally. With an effective information system, Islamic banks can respond to increasingly dynamic market needs, maintain customer loyalty, and remain steadfast in adhering to the Sharia principles that underpin their operations. Overall, technology is expected to support the development of a more advanced, efficient, and competitive Islamic banking industry.